Coralligenous assemblages of continental shelf: Multiple spatial scale variability in the western Sardinia. (1st August 2022) - Piazzi, L.; De Falco, G.; De Luca, M.; Guala, I.; Borras Palomar, A.; Conforti, A.; Pascucci, V.; Simeone, S.; Ceccherelli, G.
Abstract: Mediterranean mesophotic hard bottoms are mostly characterized by coralligenous banks. Although investigations on this habitat have increased in the last years, knowledge about its structure and spatial variability is still very limited as most studies are focused on the description of assemblages of peculiar and small locations such as biodiversity hotspots. This study aimed at i) describing coralligenous megafauna on the western Sardinian continental shelf between 80 and 120 m of depth, ii) assessing the distribution of the dominant taxa, and iii) estimating patterns of spatial variability at different scales. The coralligenous banks were studied along five sectors of the western Sardinian continental shelf by means of Remote Operated Vehicles (ROVs) and images were analyzed to identify the main taxa or morphological groups and their abundance. Results highlighted several common patterns among sectors, with assemblages dominated by the gorgonians Eunicella cavolini and Callogorgia verticillata . On the other hand, some taxa (e.g. Callogorgia verticillata, Paramuricea hirsuta, Antipathella subpinnata, Corallium rubrum Paramuricea clavata, Poecillastra compressa and Aplidium spp.) mainly contribute to segregate the coralligenous assemblages within the considered sectors of this study. A high small-scale variability was also observed. The presence of extensive and well diversified mesophotic animal forests stresses the importance to improve the conservation of the western Sardinian continental shelf. Highlights: The structure of coralligenous banks on the Sardinian continental shelf was described. Patterns of spatial variability at different scales were estimated. Sardinian coralligenous bank assemblages were dominated by erect anthozoans. Sectors segregated among them due to the local abundance of different taxa.